Lab on a stick: multi-analyte cellular assays in a microfluidic dipstick. Issue 15 (4th July 2016) - Reis, Nuno M.; Pivetal, Jeremy; Loo-Zazueta, Ana L.; Barros, João M. S.; Edwards, Alexander D.
Abstract : A lab-on-a-stick concept for simple, rapid, multiplexed and quantitative cellular bioassays in a dipstick format with the benefits of microfluidics. Abstract : A new microfluidic concept for multi-analyte testing in a dipstick format is presented, termed "Lab-on-a-Stick", that combines the simplicity of dipstick tests with the high performance of microfluidic devices. Lab-on-a-stick tests are ideally suited to analysis of particulate samples such as mammalian or bacterial cells, and capable of performing multiple different parallel microfluidic assays when dipped into a single sample with results recorded optically. The utility of this new diagnostics format was demonstrated by performing three types of multiplex cellular assays that are challenging to perform in conventional dipsticks: 1) instantaneous ABO blood typing; 2) microbial identification; and 3) antibiotic minimum inhibitory (MIC) concentration measurement. A pressure balance model closely predicted the superficial flow velocities in individual capillaries, that were overestimated by up to one order of magnitude by the Lucas–Washburn equation conventionally used for wicking in cylindrical pores. Lab-on-a-stick provides a cost-effective, simple, portable and flexible multiplex platform for a range of assays, and will deliver a new generation of advanced yet affordable point-of-care tests for global diagnostics.